Light transmission performance of translucent concrete building envelope. Issue 1 (1st January 2020) - Huang, Baofeng
Abstract: Energy efficient building envelopes are essential for sustainable development in civil engineering and architecture. In this preliminary investigation, a structural building envelope that is load bearing is developed for daylight harvesting. A translucent concrete panel (TCP) design is constructed using optical fibers (OFs) to transmit light and common concrete mix design. A steel mesh is embedded in the TCP to increase its structural load bearing capacity. It has the potential to save energy and reduce carbon footprint by collecting, channeling and eventually scattering the sunlight. Constructability issues including mechanical and optical losses are analyzed and discussed. Numerical models of the single OF and the whole TCP are developed using ray tracing software and the light transmission mechanisms are analyzed. Nonimaging sunlight collectors, namely compound parabolic concentrator (CPC), together with the OFs represent an efficient system for harvesting and guiding the sunlight into the interior spaces. The light transmission of a model made out of a CPC and an OF is evaluated from an energy efficiency point of view.